EFFECT OF DIGITAL BANKING ON CONSUMER SATISFACTION - AKAO LILIAN (Uganda Christian University, 2025)
The study evaluated how customer satisfaction at the Opportunity Bank Mukono branch was affected by digital banking. The following goals served as the study's compass: to determine how customer satisfaction at Opportunity Bank Mukono Branch is impacted by the speed of digital transactions; to evaluate the impact of accessibility to digital banking on customer satisfaction at Opportunity Bank Mukono Branch; and to investigate the impact of digital banking's adaptability on customer satisfaction. The descriptive survey design was modified for the investigation. According to Amin (2005), the survey design is a technique that entails gathering data from members of a target population while taking into account the population's present situation in relation to the research variables The target population of this study was 125 and the sample size was 96. The results show that speed of digital transactions has a significant impact on consumer satisfaction (mean range: 3.73–4.06), with ease of transactions and round-the-clock access being important factors. Although there are obstacles to online banking, accessibility to digital banking has a significant impact on satisfaction (mean range: 3.68–3.98), especially through handy mobile banking. Digital banking's adaptability has a moderate impact on customer satisfaction (mean range: 3.35–3.61), with obstacles including complicated updates and low digital literacy lowering agreement. The Opportunity Bank Mukono Branch was advised to make an investment in a strong IT infrastructure in order to reduce transaction failures and network delays. In order to target underserved clients, the bank should also increase the number of mobile banking access points and collaborate with mobile money agents.
Undergraduate